A method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder

Through technical means such as electrolytic treatment and aeration, the problem of recovering valuable metal ions of lithium iron phosphate and ternary lithium batteries in the existing technology has been solved, and an efficient and environmentally friendly recycling process has been achieved, which has improved the recovery rate and product quality.

CN119240758BActive Publication Date: 2025-03-14CHANGSHA DESIGN & RES INST OF CHEM IND MIN
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411764140.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-14
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently recover valuable metal ions from lithium iron phosphate batteries and ternary lithium batteries without introducing impurity ions, and there are safety hazards and high cost problems.

Method used

By making lithium iron phosphate black powder and ternary lithium battery black powder into slurries, electrolytic treatment is performed using inert electrodes, combined with the use of aeration and complexing agents, efficient recovery and separation of valuable metal ions are achieved, and the need to add oxidants and reducing agents is avoided.

Benefits of technology

It has achieved efficient recycling of valuable elements in lithium iron phosphate and ternary lithium battery black powder, improved the recycling rate, ensured product quality, simple process, good environmental protection, and good economicality, and is suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder, comprising the following steps: (1) preparing lithium iron phosphate black powder slurry and ternary lithium battery black powder slurry; (2) soaking an inert electrode in the lithium iron phosphate black powder slurry; soaking another inert electrode in the ternary lithium battery black powder slurry; (3) applying power to electrolyze; (4) adding alkali to the electrolyte to adjust the pH, react, then heat the reaction, and separate the solid and liquid; (5) adding iron powder to replace copper ions; (6) adding alkali to adjust the pH, then aerate the reaction, and separate the solid and liquid; (7) adding a complexing agent; (8) adding alkali solution, reacting, controlling the pH at the end of the reaction, aging, and centrifuging; (9) concentrating the filtrate, adjusting the pH, and heating the reaction, and centrifuging to obtain lithium carbonate. The present invention can avoid the safety hazard of direct electrolysis of hydrogen ions at the cathode to precipitate a large amount of hydrogen, does not require the addition of additional oxidants and reductants, saves reagent costs, and has a relatively simple process and is easy to control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of recycling and resource utilization of lithium iron phosphate power batteries and ternary lithium batteries, and in particular to a method for simultaneously recycling retired lithium iron phosphate and ternary lithium battery black powder. Background Art

[0002] At present, ternary lithium batteries and lithium iron phosphate batteries occupy almost all market shares in the market. Ternary lithium batteries have advantages such as high energy density, good low temperature resistance, and long life, while lithium iron phosphate batteries have advantages such as good safety performance, small size and light weight, and no memory effect. The service life of power batteries is generally 5 to 8 years. The nickel, cobalt, manganese, lithium, graphite, etc. in retired batteries will be abandoned as resources, which will cause huge waste.

[0003] In the future, with the rapid development of new energy electric vehicles and new energy hybrid vehicles, the output of power lithium-ion batteries will surely increase significantly. As the life of power lithium-ion batteries ends, a large number of waste power lithium-ion batteries will inevitably be generated. Therefore, the recycling technology of ternary lithium batteries and LiFePO4 batteries has great practical and economic value.

[0004] The main components of a battery are a negative electrode, a positive electrode, a separator and an electrolyte. In a lithium-ion battery, the fully discharged lithium element mainly exists in the positive electrode of the battery, and the positive electrode material is the most valuable part of the waste lithium-ion battery.

[0005] At present, there is little research on the joint recycling of lithium iron phosphate batteries and ternary lithium batteries in the market, and there is no process route that can efficiently recycle both without introducing impurity ions. This is because the recycling of lithium iron phosphate batteries requires the addition of oxidants to oxidize the divalent ferrous iron inside into trivalent iron to increase the leaching rate of lithium ions. Ternary lithium batteries, on the other hand, require pretreatment of battery black powder through reduction roasting or other methods, and then add leaching agents after reducing high-valent metal ions to achieve the purpose of front-end lithium extraction and improve the recovery rate of lithium ions. After that, the valuable elements inside are recovered step by step through extraction and other methods, or directly synthesized into ternary precursors.

[0006] A Chinese patent application with publication number CN117821751A discloses a method for the combined leaching and recycling of waste lithium iron phosphate and ternary material positive electrode powder. However, the addition of Lewis acid (mainly iron salt solutions such as ferric sulfate, ferric chloride, and ferric nitrate) introduces other acid radical ions and iron elements, which makes it difficult to ensure the quality of the product, and a large amount of waste salt cannot be processed.

[0007] The Chinese patent application with publication number CN115954574A discloses a method for synergistically recovering waste lithium iron phosphate batteries and waste ternary lithium ion battery positive electrode powder, using nitric acid and acetic acid as leaching agents to oxidize the divalent iron in the lithium iron phosphate and generate nitric oxide at the same time, which reduces the nickel, cobalt and manganese in the lithium nickel cobalt manganese oxide to obtain a leaching mother liquor of mixed electrode materials. However, the nitric acid used is relatively dangerous, and the generated gas will pollute the atmosphere and easily cause serious health threats to operators.

[0008] A Chinese patent application with publication number CN118398944A discloses a method for the joint recovery of waste ternary lithium battery positive electrode powder and lithium iron phosphate battery positive electrode powder. The ferrous ions in the mixed solution are oxidized into trivalent ferrous ions by adding a leaching agent and an oxidant, and a ternary precursor is prepared by co-precipitation with transition metal oxalate. However, the quality of the ternary precursor material generated by high-temperature calcination in a muffle furnace cannot be guaranteed, and the components of the jointly recovered ternary precursor are relatively complex and difficult to recycle.

[0009] The Chinese patent with publication number CN111411366B discloses a method for recovering metal ions from lithium iron phosphate waste by solid phase electrolysis, using dried lithium iron phosphate slurry as anode and dilute phosphoric acid as electrolyte, and accelerating the leaching rate of lithium ions by electrolysis. However, phosphoric acid is relatively expensive and is a weak acid, resulting in a low leaching rate of lithium ions, which causes a waste of valuable elements. In addition, this method has high purity requirements for lithium iron phosphate raw materials, greatly increasing the cost of black powder pretreatment, which is not conducive to industrial promotion. Moreover, it uses phosphoric acid as an electrolyte, its divalent iron loses electrons, the cathode hydrogen ions gain electrons, and the cathode precipitates a large amount of hydrogen, which has safety hazards, and explosion-proof measures are required for hydrogen precipitation; stainless steel electrodes are used, phosphoric acid is used as an electrolyte, if the concentration and reaction conditions are not properly controlled, the stainless steel electrodes will also react with phosphoric acid, and other acids must be used additionally when the stainless steel electrodes are cleaned.

[0010] The Chinese patent application with publication number CN117383588A discloses a method for recycling retired lithium iron phosphate batteries by electrochemical yin-yang coupling wet method, wherein an electrochemical system including a working electrode, a counter electrode and a reference electrode is used to electrolyze the electrolyte, wherein the working electrode and the counter electrode are activated graphene aerogel GA electrodes; the reference electrode is an Ag / AgCl electrode. The cost of the reference electrode silver electrode used is too high, and the processing volume is not large, which is not conducive to promotion and use; the activated graphene aerogel GA is prepared by boiling the graphene aerogel GA with HNO3 and roasting with N2, which has a high processing cost, is very dangerous to operate, and the quality of the finished electrode is not easy to control.

[0011] In order to solve the above technical problems, it is urgently necessary to propose a method that can efficiently recover the valuable metal ions in the positive electrode powder of lithium iron phosphate batteries and the positive electrode powder of ternary lithium batteries. Summary of the invention

[0012] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for recycling retired lithium iron phosphate and ternary lithium battery black powder with a relatively simple process and environmental protection.

[0013] The technical solution adopted by the present invention to solve the technical problem is a method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder, comprising the following steps:

[0014] (1) preparing lithium iron phosphate black powder and ternary lithium battery black powder into slurries respectively, thereby obtaining lithium iron phosphate black powder slurry and ternary lithium battery black powder slurry respectively;

[0015] (2) soaking an inert electrode in the lithium iron phosphate black powder slurry obtained in step (1) (preferably soaking time is more than 2 minutes), taking it out and drying it to obtain electrode A, and electrode A is connected to the positive electrode of the power supply as an anode; soaking another inert electrode in the ternary lithium battery black powder slurry obtained in step (1) (preferably soaking time is more than 2 minutes), taking it out and drying it to obtain electrode B, and electrode B is connected to the negative electrode of the power supply as a cathode;

[0016] If the inert electrode's immersion time is too short, the black powder slurry will not adhere completely, affecting the treatment effect.

[0017] (3) placing the electrode A and the electrode B obtained in step (2) in an electrolyte, and then applying power to perform electrolysis for a period of time; after the electrolysis, taking out the electrode A and the electrode B, filtering the electrolyte, and obtaining a filtered electrolyte;

[0018] The filtered substances are mainly composed of graphite slag or some other insoluble matter;

[0019] (4) adding alkali to the electrolyte filtered in step (3) to adjust the pH, reacting for a period of time, then heating to react for a period of time, and then separating the solid and liquid to obtain a filter residue and a filtrate, wherein the filter residue is the iron phosphate in the electrolyte;

[0020] (5) adding an excess amount of iron powder to the filtrate obtained in step (4) to replace the copper ions, continuing the reaction and stirring, removing the copper ions in the filtrate by replacing the copper ions with iron, and then filtering to obtain copper-iron slag and the filtrate;

[0021] (6) adding alkali to the filtrate obtained in step (5) to adjust the pH, then aerating and continuing the reaction, and then standing to separate the solid and liquid to obtain a filter residue and a filtrate, wherein the filter residue is ferric hydroxide and aluminum hydroxide;

[0022] The present invention adopts aeration to make the solution mixing more uniform, and aeration makes the relevant ions of the filtrate oxidized more completely, and iron hydroxide and aluminum hydroxide are obtained by processing at the same time, without the need for an oxidant, and has good economic efficiency.

[0023] (7) adding a complexing agent to the filtrate obtained in step (6) to complex the nickel, cobalt and manganese in the filtrate;

[0024] (8) adding alkaline solution to the filtrate to which the complexing agent is added in step (7), reacting, controlling the pH at the end point of the reaction to be 11-12 (preferably 11.4-11.6), aging, and centrifuging to obtain a ternary precursor and a filtrate;

[0025] (9) The filtrate in step (8) is concentrated, and after concentration, carbon dioxide or sodium carbonate is introduced to adjust the pH, and the mixture is heated and reacted for a period of time, and then centrifuged to obtain lithium carbonate.

[0026] Furthermore, in step (1), the lithium iron phosphate black powder is obtained by dismantling and crushing retired lithium iron phosphate batteries. The ternary lithium battery black powder is obtained by dismantling and crushing retired ternary lithium batteries. Both can be purchased from the market through regular commercial channels.

[0027] Furthermore, in step (1), water is added to lithium iron phosphate black powder and ternary lithium battery black powder to prepare lithium iron phosphate black powder slurry and ternary lithium battery black powder slurry respectively. After adding water, the prepared slurry is stirred for 40-60 minutes to make it more evenly dispersed. The liquid-to-solid ratio of lithium iron phosphate black powder slurry and ternary lithium battery black powder slurry is 5-15 ml / g (preferably 8-12 ml / g).

[0028] Furthermore, in step (2), the inert electrode is at least one of a carbon felt electrode, a graphite felt electrode, a nanocarbon film electrode, a conductive glass electrode, a high-purity graphite electrode, etc. Preferably, the lateral resistivity of the electrode is 5-20Ω·mm, and the longitudinal resistivity of the electrode is 5-20Ω·mm. The present invention selects an electrode with a lower resistivity in order to ensure the conductivity of the system; if the resistivity is too high, the voltage needs to be increased to ensure the conductivity of the system, which firstly results in high energy consumption and secondly poor safety, which is not conducive to operation.

[0029] Furthermore, in step (2), the types of the inert electrodes of electrode A and electrode B may be different or the same. However, it is preferred that the types of the inert electrodes of electrode A and electrode B are the same, because the same inert electrodes can ensure uniform conductivity and little difference in resistance.

[0030] Furthermore, in step (2), the preferred inert electrode is a graphite felt electrode. The inert electrodes used in the present invention are all commercially available products, easy to obtain, and have lower costs; and they have better adhesion, better conductivity, and faster processing speed. The greater the porosity of the inert electrode, the more slurry it can load and the greater the amount of processing.

[0031] Furthermore, in step (2), the inert electrode is taken out after being soaked and dried. The drying time is 4-5 hours, and the drying temperature is 70-90°C. The preferred drying time is 4 hours, and the drying temperature is 75°C. For electrodes with slurry attached, if the drying time is too short, the drying will not be complete, and the slurry will drip; if the drying time is too long, cracks will appear in the slurry, which will affect some of the conductive properties, resulting in some slurry not being completely electrolyzed, and there will be loss of valuable metal ions; if the drying temperature is too high, the slurry will lose water too quickly, which will also affect the electrode performance.

[0032] Furthermore, in step (2), the mass ratio of the lithium iron phosphate black powder slurry loaded on the dried electrode A to the ternary lithium battery black powder slurry loaded on the dried electrode B is (5-8): 1. At this mass ratio, the lithium iron phosphate black powder is slightly excessive, which can ensure that the nickel, cobalt and manganese in the ternary lithium battery black powder are reduced to a lower valence state.

[0033] Furthermore, in step (3), the electrolyte is at least one of sulfuric acid, nitric acid, and phosphoric acid. The concentration of the electrolyte is 0.05-0.10 mol / L. The electrolysis is performed at room temperature (25°C). The electrolysis device uses direct current, and the direct current voltage is 0.1-2.5V. The electrolysis time is 30-120min. Among them, the preferred electrolyte is sulfuric acid, the concentration is 0.10 mol / L, and the electrolysis time is 40min.

[0034] Furthermore, in step (3), the electrode A and the electrode B obtained in step (2) are placed in the electrolyte and soaked for a period of time before being energized for electrolysis. It is further preferred that the soaking time is 30-120 minutes (more preferably 60 minutes). Studies have shown that soaking for a period of time helps increase the electrolysis efficiency.

[0035] Furthermore, in step (4), from the economic point of view and the recovery effect, the alkali is preferably at least one of ammonia water, sodium hydroxide, sodium carbonate, etc. Preferably, the alkali is added to adjust the pH to 1.5-2.0. This range is the pH value range for the precipitation of iron phosphate. If it is too low, no precipitation will occur, and if it is too high, other ions will precipitate, resulting in the loss of valuable metals.

[0036] Furthermore, in step (4), after adding a base to adjust the pH, the reaction is carried out at room temperature (preferably for 20-40 minutes), and then the solution is heated to 70-80°C, the reaction is continued for 3.5-5 hours, and FePO4·2H2O is obtained after separation by filtration.

[0037] Furthermore, in step (5), the amount of iron powder added is 1.2-4 times (preferably 2.5 times) the amount of copper ion in the system, the reaction is continued for 1-3 hours, and the stirring rate is 60-200 r / min. The preferred reaction time is 2.5 hours and the stirring rate is 80 r / min.

[0038] Furthermore, in step (6), from the economic point of view and the recovery effect, the alkali is at least one of ammonia water, sodium hydroxide, sodium carbonate, etc. (preferably sodium hydroxide). Preferably, the alkali is added to adjust the pH to 5.5-6.5 (preferably pH 6). This range is the pH range for the precipitation of aluminum hydroxide and ferric hydroxide. A higher pH will lead to the precipitation loss of other valuable metal ions, and a lower pH will not form a precipitate. Aluminum hydroxide and ferric hydroxide are acidic and soluble.

[0039] Furthermore, in step (6), the aeration reaction is continued for 8-16 hours and then the mixture is allowed to stand for 8-16 hours for solid-liquid separation. Preferably, the aeration time is 12 hours and the standing time is 16 hours.

[0040] Furthermore, in step (7), the complexing agent is ammonia water. The amount of ammonia ions in the ammonia water is 1.2-1.5 times the total amount of nickel, cobalt and manganese ions in the filtrate. Ammonia mainly plays a complexing role. Continuing to add a complexing agent to the filtrate from which iron hydroxide and aluminum hydroxide are separated can cause a complexing reaction between nickel, cobalt and manganese in the filtrate. In order to allow nickel, cobalt and manganese ions to coprecipitate at a uniform and slow rate, if no complexing agent is added, the precipitation rates of nickel, cobalt and manganese ions and alkali are inconsistent, and a uniformly arranged nickel, cobalt and manganese coprecipitated ternary precursor cannot be formed.

[0041] Furthermore, in step (8), the alkali solution is a strong alkali solution, preferably a potassium hydroxide solution or a sodium hydroxide solution. The reaction time is 6-12 hours, and the aging time is 2-4 hours. The preferred reaction time is 8 hours, and the aging time is 2 hours. The main components of the ternary precursor are nickel, cobalt, and manganese hydroxides.

[0042] Furthermore, in step (9), the concentration is preferably 1 / 5-1 / 20 of the original amount.

[0043] Furthermore, in step (9), the preferred method of lithium precipitation is to introduce sodium carbonate.

[0044] Furthermore, in step (9), the pH is adjusted to above 11, the heating temperature is 80-99° C., and the reaction time is continued for 1-6 hours.

[0045] Beneficial effects of the present invention:

[0046] The resource recovery method of the present invention for recovering valuable elements from lithium iron phosphate black powder and ternary lithium battery black powder can simultaneously recover valuable elements from lithium iron phosphate black powder and ternary lithium battery black powder, and can efficiently recover all valuable elements from mixed recycled materials. When dissolving valuable elements from lithium iron phosphate black powder, an oxidant needs to be added to make Fe 2+ Oxidized to Fe 3+, thereby increasing the dissolution rate of lithium ions. When dissolving the ternary lithium battery black powder, a reducing agent needs to be added to reduce the high-valent metal ions in lithium cobalt oxide, lithium nickel oxide, and lithium manganese oxide to a lower valence state, so as to be used as the raw materials for synthesizing ternary precursors or extracted and separated into nickel sulfate, cobalt sulfate, and manganese sulfate. The leaching of lithium iron phosphate requires the use of an oxidant, while the leaching of ternary lithium battery black powder requires the use of a reducing agent. The present invention innovatively realizes the co-leaching of valuable elements in lithium iron phosphate black powder and ternary lithium battery black powder through an external electric field, ensuring the leaching rate without the need to add oxidants and reducing agents, with good economy and high technical promotion.

[0047] The resource recovery method of the present invention for jointly processing lithium iron phosphate battery black powder and ternary lithium battery black powder can improve the recovery rate of valuable metal ions in lithium ion battery black powder, and can also ensure the quality of recycled products. The process is simple and can achieve green and efficient recovery of lithium iron phosphate batteries and ternary lithium batteries.

[0048] Working principle of the present invention:

[0049] Anode working principle: Fe 2+ -e - →Fe 3+

[0050] Cathode working principle: Ni 3+ +e - →Ni 2+

[0051] Co 3+ +e - →Co 2+

[0052] Mn 3+ +e - →Mn 2+

[0053] Mn 4+ +2e - →Mn 2+

[0054] The nickel, cobalt and manganese ions of the present invention are all in a higher valence state and have stronger oxidizing properties. They can obtain electrons before hydrogen ions, and can avoid the potential safety hazard of direct electrolysis of hydrogen ions at the cathode to precipitate a large amount of hydrogen. The present invention adopts aeration to make the mixing of the solution more uniform, and aeration makes the relevant ions of the filtrate oxidized more completely. At the same time, iron hydroxide and aluminum hydroxide are obtained by processing, and no oxidant is required, which has better economy. The inert electrodes used in the present invention are all commercially available products, which are easy to obtain and have lower cost; moreover, they have better adhesion and better conductivity, and can process black powder raw materials faster. The present invention does not require the additional addition of oxidants and reductants, saves the cost of reagents, and the process is relatively simple and easy to control. DETAILED DESCRIPTION

[0055] The present invention is further described in detail below through specific examples.

[0056] The electrode used for adsorbing the mixed slurry in each embodiment is a graphite felt electrode with a porosity of 93%, a lateral resistivity of 6Ω·mm, a longitudinal resistivity of 7Ω·mm, and a thickness of 2mm.

[0057] The battery raw materials used in each example were obtained through conventional commercial channels.

[0058] In this specification, unless otherwise specified, all percentages are by weight.

[0059] The lithium iron phosphate black powder and ternary lithium battery black powder treated in the embodiment were obtained from commercial sources. They were tested and the mass fractions of lithium and iron in the lithium iron phosphate black powder were measured as shown in Table 1. The mass fractions of valuable elements in the ternary lithium battery black powder were measured as shown in Table 2.

[0060] Table 1 Mass fraction of lithium and iron in lithium iron phosphate black powder

[0061] serial number Lithium wt% Iron wt% Copper element wt% 1 3.81 27.6 1.35

[0062] Table 2 Mass fraction of valuable elements in black powder of ternary lithium battery

[0063] serial number Nickel element wt% Cobalt element wt% Manganese element wt% Lithium wt% Copper element wt% 1 28.39 2.21 2.24 4.60 1.15 Example 1

[0064] The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder in this embodiment comprises the following steps:

[0065] (1) Adding water to lithium iron phosphate black powder and ternary lithium battery black powder to prepare slurries respectively, with a liquid-to-solid ratio of 10 ml / g, stirring for 50 min to obtain lithium iron phosphate black powder slurry and ternary lithium battery black powder slurry respectively;

[0066] (2) soaking a graphite felt electrode in the lithium iron phosphate black powder slurry obtained in step (1) (soaking time 5 min), taking it out and drying it (baking at 90°C for 4 h) to obtain electrode A, and electrode A is connected to the positive electrode of the power supply as an anode; soaking another graphite felt electrode in the ternary lithium battery black powder slurry obtained in step (1) (soaking time 5 min), taking it out and drying it (baking at 90°C for 4 h) to obtain electrode B, and electrode B is connected to the negative electrode of the power supply as a cathode;

[0067] The loading amount of the slurry on the prepared working electrode was about 0.1 g cm -2 In this embodiment, the electrode A loaded with 30g of lithium iron phosphate black powder slurry and the electrode B loaded with 5g of ternary lithium battery black powder slurry were used for the reaction.

[0068] (3) Add sulfuric acid electrolyte with a concentration of 0.05 mol / L into the electrolytic cell, soak the electrode A and electrode B obtained in step (2) in the electrolyte for 30 minutes, and then conduct electrolysis for 45 minutes; electrode A is the anode and electrode B is the cathode. The DC voltage used for electrolysis is 0.5 V, and the above operations are all carried out at room temperature; after electrolysis, remove electrode A and electrode B, filter the electrolyte, and obtain the filtered electrolyte;

[0069] The ion content in the leachate was tested using an inductively coupled plasma optical emission spectrometer (ICP-OES). The results showed that the comprehensive leaching rate of lithium was 84%, the leaching rate of iron was 83%, the leaching rate of nickel was 84%, the leaching rate of cobalt was 83%, and the leaching rate of manganese was 84%.

[0070] (4) Adding 25% by mass of ammonia water to the electrolyte after filtering in step (3) to control the pH to 2, reacting for 40 minutes, and then heating to 80° C. for 4 hours. After the reaction is completed, filtering and separating to obtain a filter residue and a filtrate, wherein the filter residue is FePO4·2H2O.

[0071] (5) adding excess iron powder to the filtrate obtained in step (4) to replace copper ions, continuing the reaction and stirring (stirring speed is 70 r / min, reaction time is 2 h), removing copper ions in the filtrate by replacing copper ions with iron, and then filtering to obtain copper-iron slag and filtrate; the filter residue is mainly copper-iron slag, and the copper ion content in the filtrate is 3 mg / L by ICP detection;

[0072] The amount of iron powder added is 1.5 times the amount of copper ion in the system;

[0073] (6) Sodium hydroxide was added to the filtrate obtained in step (5) to adjust the pH to 6, the temperature was raised to 85°C, and aeration was continued for 8 hours with an aeration rate of 0.5 m 3 / h, then let it stand for 8h, separate the solid and liquid to obtain a filter residue and a filtrate, the filter residue is a mixed product of ferric hydroxide and aluminum hydroxide; the iron ion content in the filtrate is ≤10mg / L and the aluminum ion content is ≤10mg / L by ICP detection;

[0074] (7) adding a complexing agent, aqueous ammonia, to the filtrate obtained in step (6) to complex the nickel, cobalt and manganese in the filtrate;

[0075] The amount of ammonium ions in the ammonia water is 1.2 times the total amount of nickel, cobalt and manganese ions in the filtrate;

[0076] The nickel, cobalt and manganese of the present invention have stronger oxidizability and can obtain electrons before hydrogen ions, thereby avoiding the potential safety hazard of cathode hydrogen evolution.

[0077] (8) adding alkaline sodium hydroxide solution to the filtrate to which the complexing agent was added in step (7), adjusting the temperature to 65° C., reacting for 8 hours, controlling the pH at the end point of the reaction to be 11.5, aging for 2 hours, and centrifuging to obtain a ternary precursor and a filtrate;

[0078] (9) The filtrate in step (8) is concentrated to 1 / 5 of the original volume. After concentration, sodium carbonate is introduced to adjust the pH to 11, and the mixture is heated to 80° C. and reacted for 3 h. The mixture is centrifuged to obtain lithium carbonate. Example 2

[0079] The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder in this embodiment comprises the following steps:

[0080] (1) Adding water to lithium iron phosphate black powder and ternary lithium battery black powder to prepare slurries respectively, with a liquid-to-solid ratio of 10 ml / g, stirring for 60 min to obtain lithium iron phosphate black powder slurry and ternary lithium battery black powder slurry respectively;

[0081] (2) soaking a carbon felt electrode in the lithium iron phosphate black powder slurry obtained in step (1) (soaking time 5 min), taking it out and drying it (baking at 90°C for 5 h) to obtain electrode A, and electrode A is connected to the positive electrode of the power supply as an anode; soaking another carbon felt electrode in the ternary lithium battery black powder slurry obtained in step (1) (soaking time 5 min), taking it out and drying it (baking at 90°C for 5 h) to obtain electrode B, and electrode B is connected to the negative electrode of the power supply as a cathode;

[0082] The loading amount of the slurry on the prepared working electrode was about 0.1 g cm -2 In this embodiment, the electrode A loaded with 35g of lithium iron phosphate black powder slurry and the electrode B loaded with 5g of ternary lithium battery black powder slurry were used for the reaction.

[0083] (3) Add sulfuric acid electrolyte with a concentration of 0.08 mol / L into the electrolytic cell, soak the electrode A and electrode B obtained in step (2) in the electrolyte for 45 minutes, and then conduct electrolysis for 45 minutes; electrode A is the anode and electrode B is the cathode. The DC voltage used for electrolysis is 1.0 V, and the above operations are all carried out at room temperature; after electrolysis, remove electrode A and electrode B, filter the electrolyte, and obtain the filtered electrolyte;

[0084] The ion content in the leachate was tested using an inductively coupled plasma optical emission spectrometer (ICP-OES). The results showed that the comprehensive leaching rate of lithium was 87%, the leaching rate of iron was 87%, the leaching rate of nickel was 89%, the leaching rate of cobalt was 89%, and the leaching rate of manganese was 90%.

[0085] (4) Adding 25% by mass of ammonia water to the electrolyte after filtering in step (3) to control the pH to 2, reacting for 40 minutes, and then heating to 80° C. for 4 hours. After the reaction is completed, filtering and separating to obtain a filter residue and a filtrate, wherein the filter residue is FePO4·2H2O.

[0086] (5) adding excess iron powder to the filtrate obtained in step (4) to replace copper ions, continuing the reaction and stirring (stirring speed is 70 r / min, reaction time is 2.5 h), removing copper ions in the filtrate by replacing copper ions with iron, and then filtering to obtain copper-iron slag and filtrate; the filter residue is mainly copper-iron slag, and the copper ion content in the filtrate is 2.2 mg / L by ICP detection;

[0087] The amount of iron powder added is twice the amount of copper ion in the system;

[0088] (6) Sodium hydroxide was added to the filtrate obtained in step (5) to adjust the pH to 6, the temperature was raised to 85°C, and aeration was continued for 8 hours with an aeration rate of 0.5 m 3 / h, then let it stand for 8h, separate the solid and liquid to obtain the filter residue and filtrate, the filter residue is the mixed product of ferric hydroxide and aluminum hydroxide, and the iron ion content in the filtrate is ≤10mg / L and the aluminum ion content is ≤10mg / L by ICP detection;

[0089] (7) adding a complexing agent ammonia water to the filtrate obtained in step (6) to complex the nickel, cobalt and manganese in the filtrate; the amount of ammonium ions in the ammonia water is 1.3 times the total amount of nickel, cobalt and manganese ions in the filtrate;

[0090] The nickel, cobalt and manganese of the present invention have stronger oxidizability and can obtain electrons before hydrogen ions, thereby avoiding the potential safety hazard of cathode hydrogen evolution.

[0091] (8) adding alkaline sodium hydroxide solution to the filtrate to which the complexing agent was added in step (7), adjusting the temperature to 65° C., reacting for 8 hours, controlling the pH at the end point of the reaction to be 11.5, aging for 2 hours, and centrifuging to obtain a ternary precursor and a filtrate;

[0092] (9) The filtrate in step (8) is concentrated to 1 / 5 of the original volume. After concentration, sodium carbonate is introduced to adjust the pH to 12, and the mixture is heated to 90° C. The reaction is continued for 2 h, and then centrifuged to obtain lithium carbonate. Example 3

[0093] The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder in this embodiment comprises the following steps:

[0094] (1) Adding water to lithium iron phosphate black powder and ternary lithium battery black powder to prepare slurries respectively, with a liquid-to-solid ratio of 10 ml / g, stirring for 40 min to obtain lithium iron phosphate black powder slurry and ternary lithium battery black powder slurry respectively;

[0095] (2) soaking the nano-carbon film electrode in the lithium iron phosphate black powder slurry obtained in step (1) (soaking time 5 min), taking it out and drying it (baking at 90°C for 5 h) to obtain electrode A, and electrode A is connected to the positive pole of the power supply as an anode; soaking another nano-carbon film electrode in the ternary lithium battery black powder slurry obtained in step (1) (soaking time 5 min), taking it out and drying it (baking at 90°C for 5 h) to obtain electrode B, and electrode B is connected to the negative pole of the power supply as a cathode;

[0096] The loading amount of the slurry on the prepared working electrode was about 0.1 g cm -2 In this embodiment, the electrode A loaded with 35g of lithium iron phosphate black powder slurry and the electrode B loaded with 5g of ternary lithium battery black powder slurry were used for the reaction.

[0097] (3) Add sulfuric acid electrolyte with a concentration of 0.1 mol / L into the electrolytic cell, soak the electrode A and electrode B obtained in step (2) in the electrolyte for 60 minutes, and then conduct electrolysis for 60 minutes; electrode A is the anode and electrode B is the cathode. The DC voltage used for electrolysis is 2.0 V, and the above operations are all carried out at room temperature; after electrolysis, remove electrode A and electrode B, filter the electrolyte, and obtain the filtered electrolyte;

[0098] The ion content in the leachate was tested using an inductively coupled plasma optical emission spectrometer (ICP-OES). The results showed that the comprehensive leaching rate of lithium was 94%, the leaching rate of iron was 95%, the leaching rate of nickel was 97%, the leaching rate of cobalt was 97%, and the leaching rate of manganese was 97%.

[0099] (4) Adding 25% by mass of ammonia water to the electrolyte after filtering in step (3) to control the pH to 2, reacting for 40 minutes, and then heating to 80° C. for 4 hours. After the reaction is completed, filtering and separating to obtain a filter residue and a filtrate, wherein the filter residue is FePO4·2H2O.

[0100] (5) adding excess iron powder to the filtrate obtained in step (4) to replace copper ions, continuing the reaction and stirring (stirring speed is 80 r / min, reaction time is 2.5 h), removing copper ions in the filtrate by replacing copper ions with iron, and then filtering to obtain copper-iron slag and filtrate; the filter residue is mainly copper-iron slag, and the copper ion content in the filtrate is 2 mg / L by ICP detection;

[0101] The amount of iron powder added is 2.5 times the amount of copper ion in the system;

[0102] (6) Sodium hydroxide was added to the filtrate obtained in step (5) to adjust the pH to 6, the temperature was raised to 85°C, and aeration was continued for 8 hours with an aeration rate of 0.5 m 3 / h, then let it stand for 8h, separate the solid and liquid to obtain the filter residue and filtrate, the filter residue is the mixed product of ferric hydroxide and aluminum hydroxide, and the iron ion content in the filtrate is ≤10mg / L and the aluminum ion content is ≤10mg / L by ICP detection;

[0103] (7) adding a complexing agent, ammonia water, to the filtrate obtained in step (6) to complex the nickel, cobalt and manganese in the filtrate; the amount of ammonium ions in the ammonia water is 1.2 times the total amount of nickel, cobalt and manganese ions in the filtrate;

[0104] The nickel, cobalt and manganese of the present invention have stronger oxidizability and can obtain electrons before hydrogen ions, thereby avoiding the potential safety hazard of cathode hydrogen evolution.

[0105] (8) adding alkaline sodium hydroxide solution to the filtrate to which the complexing agent was added in step (7), adjusting the temperature to 65° C., reacting for 8 hours, controlling the pH at the end point of the reaction to be 12.0, aging for 2 hours, and centrifuging to obtain a ternary precursor and a filtrate;

[0106] (9) The filtrate in step (8) is concentrated to 1 / 5 of the original volume. After concentration, sodium carbonate is introduced to adjust the pH to 12, and the mixture is heated to 90° C. The reaction is continued for 3 h, and then centrifuged to obtain lithium carbonate. Example 4

[0107] The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder in this embodiment comprises the following steps:

[0108] (1) Adding water to lithium iron phosphate black powder and ternary lithium battery black powder to prepare slurries respectively, with a liquid-to-solid ratio of 10 ml / g, stirring for 60 min to obtain lithium iron phosphate black powder slurry and ternary lithium battery black powder slurry respectively;

[0109] (2) soaking the graphite felt electrode in the lithium iron phosphate black powder slurry obtained in step (1) (soaking time 5 min), taking it out and drying it (baking at 90°C for 5 h) to obtain electrode A, and electrode A is connected to the positive electrode of the power supply as an anode; soaking another graphite felt electrode in the ternary lithium battery black powder slurry obtained in step (1) (soaking time 5 min), taking it out and drying it (baking at 90°C for 5 h) to obtain electrode B, and electrode B is connected to the negative electrode of the power supply as a cathode;

[0110] The loading amount of the slurry on the prepared working electrode was about 0.1 g cm -2 In this embodiment, the electrode A loaded with 35g of lithium iron phosphate black powder slurry and the electrode B loaded with 5g of ternary lithium battery black powder slurry were used for the reaction.

[0111] (3) Add sulfuric acid electrolyte with a concentration of 0.08 mol / L into the electrolytic cell, soak the electrode A and electrode B obtained in step (2) in the electrolyte for 60 minutes, and then conduct electrolysis for 60 minutes; electrode A is the anode and electrode B is the cathode. The DC voltage used for electrolysis is 2.2 V, and the above operations are all carried out at room temperature; after electrolysis, remove electrode A and electrode B, filter the electrolyte, and obtain the filtered electrolyte;

[0112] The ion content in the leachate was tested using an inductively coupled plasma optical emission spectrometer (ICP-OES). The results showed that the comprehensive leaching rate of lithium was 95%, the leaching rate of iron was 95%, the leaching rate of nickel was 98%, the leaching rate of cobalt was 98%, and the leaching rate of manganese was 98%.

[0113] (4) Adding 25% by mass of ammonia water to the electrolyte after filtering in step (3) to control the pH to 2, reacting for 40 minutes, and then heating to 85° C. for 4 hours. After the reaction is completed, filtering and separating to obtain a filter residue and a filtrate, wherein the filter residue is FePO4·2H2O.

[0114] (5) adding excess iron powder to the filtrate obtained in step (4) to replace copper ions, continuing the reaction and stirring (stirring speed is 80 r / min, reaction time is 2.5 h), removing copper ions in the filtrate by replacing copper ions with iron, and then filtering to obtain copper-iron slag and filtrate; the filter residue is mainly copper-iron slag, and the copper ion content in the filtrate is 2.0 mg / L by ICP detection;

[0115] The amount of iron powder added is 1.5 times the amount of copper ion in the system;

[0116] (6) Sodium hydroxide was added to the filtrate obtained in step (5) to adjust the pH to 6, the temperature was raised to 85°C, and aeration was continued for 8 hours with an aeration rate of 1.0 m 3 / h, then let it stand for 8h, separate the solid and liquid to obtain the filter residue and filtrate, the filter residue is the mixed product of ferric hydroxide and aluminum hydroxide, and the iron ion content in the filtrate is ≤10mg / L and the aluminum ion content is ≤10mg / L by ICP detection;

[0117] (7) adding a complexing agent, aqueous ammonia, to the filtrate obtained in step (6) to complex the nickel, cobalt and manganese in the filtrate;

[0118] The amount of ammonium ions in the ammonia water is 1.2 times the total amount of nickel, cobalt and manganese ions in the filtrate;

[0119] The nickel, cobalt and manganese of the present invention have stronger oxidizability and can obtain electrons before hydrogen ions, thereby avoiding the potential safety hazard of cathode hydrogen evolution.

[0120] (8) adding alkaline sodium hydroxide solution to the filtrate to which the complexing agent was added in step (7), adjusting the temperature to 65° C., reacting for 8 hours, controlling the pH at the end point of the reaction to be 11.5, aging for 2 hours, and centrifuging to obtain a ternary precursor and a filtrate;

[0121] (9) The filtrate in step (8) is concentrated to 1 / 20 of the original volume. After concentration, sodium carbonate is introduced to adjust the pH to 12, and the mixture is heated to 60° C. and reacted for 5 h. The mixture is centrifuged to obtain lithium carbonate.

Claims

1. A method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder, characterized in that: The following steps are involved: (1) preparing lithium iron phosphate black powder and ternary lithium battery black powder into slurries respectively, thereby obtaining lithium iron phosphate black powder slurry and ternary lithium battery black powder slurry respectively; (2) soaking an inert electrode in the lithium iron phosphate black powder slurry obtained in step (1), taking it out and drying it to obtain electrode A, and electrode A is connected to the positive electrode of the power supply as an anode; soaking another inert electrode in the ternary lithium battery black powder slurry obtained in step (1), taking it out and drying it to obtain electrode B, and electrode B is connected to the negative electrode of the power supply as a cathode; In step (2), the inert electrode is at least one of a carbon felt electrode, a graphite felt electrode, a nanocarbon film electrode, a conductive glass electrode, and a high-purity graphite electrode; (3) placing the electrode A and the electrode B obtained in step (2) in an electrolyte, and then applying electricity to electrolyze for a period of time; After electrolysis, take out electrode A and electrode B, filter the electrolyte, and obtain a filtered electrolyte; In step (3), the electrolyte is at least one of sulfuric acid, nitric acid, and phosphoric acid; In step (3), the electrode A and the electrode B obtained in step (2) are placed in an electrolyte and immersed for a period of time, and then powered on for electrolysis; (4) adding alkali to the electrolyte filtered in step (3) to adjust the pH, reacting for a period of time, then heating to react for a period of time, and then separating the solid and liquid to obtain a filter residue and a filtrate, wherein the filter residue is the iron phosphate in the electrolyte; (5) adding excess iron powder to the filtrate obtained in step (4) to replace copper ions, continuing the reaction and stirring, and then filtering to obtain copper-iron slag and filtrate; (6) adding alkali to the filtrate obtained in step (5) to adjust the pH, then aerating and continuing the reaction, and then standing to separate the solid and liquid to obtain a filter residue and a filtrate, wherein the filter residue is ferric hydroxide and aluminum hydroxide; (7) adding a complexing agent to the filtrate obtained in step (6) to complex the nickel, cobalt and manganese in the filtrate; (8) adding alkaline solution to the filtrate to which the complexing agent is added in step (7), reacting, controlling the pH at the end point of the reaction to be 11-12, aging, and centrifuging to obtain a ternary precursor and a filtrate; (9) The filtrate in step (8) is concentrated, and after concentration, carbon dioxide or sodium carbonate is introduced to adjust the pH, and the mixture is heated and reacted for a period of time, and then centrifuged to obtain lithium carbonate.

2. The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder according to claim 1, characterized in that: In step (1), water is added to lithium iron phosphate black powder and ternary lithium battery black powder to prepare lithium iron phosphate black powder slurry and ternary lithium battery black powder slurry respectively; and / or the liquid-to-solid ratio of the lithium iron phosphate black powder slurry and the ternary lithium battery black powder slurry is 5-15 ml / g.

3. The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder according to claim 1 or 2, characterized in that: In step (2), the inert electrode is taken out after being soaked and dried; and / or, in step (2), the mass ratio of the lithium iron phosphate black powder slurry loaded on the electrode A after drying and the ternary lithium battery black powder slurry loaded on the electrode B after drying is (5-8):

1.

4. The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder according to claim 1 or 2, characterized in that: In step (2), the inert electrode is immersed in the lithium iron phosphate black powder slurry obtained in step (1) and in the ternary lithium battery black powder slurry obtained in step (1) for a time of more than 2 minutes.

5. The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder according to claim 1 or 2, characterized in that: In step (4), alkali is added to adjust the pH to 1.5-2.0; and / or, in step (4), alkali is added to adjust the pH and then reacted at room temperature, then the solution is heated to 70-80°C, the reaction is continued for 3.5-5 hours, and FePO4·2H2O is obtained by filtration and separation; and / or, in step (5), the amount of iron powder added is 1.2-4 times the amount of copper ion in the system, the reaction is continued for 1-3 hours, and the stirring rate is 60-200 r / min.

6. The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder according to claim 1 or 2, characterized in that: In step (6), alkali is added to adjust the pH to 5.5-6.5; and / or, in step (6), aeration is continued for 8-16 hours, and then the mixture is allowed to stand for 8-16 hours to separate the solid and liquid.

7. The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder according to claim 1 or 2, characterized in that: In step (7), the complexing agent is aqueous ammonia; and / or, in step (8), the alkali solution is a strong alkali solution, the reaction time is 6-12 hours, and the aging time is 2-4 hours.

8. The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder according to claim 7, characterized in that: In step (7), the amount of ammonium ions in the ammonia water is 1.2-1.5 times the total amount of nickel, cobalt and manganese ions in the filtrate.

9. The method for simultaneously recovering retired lithium iron phosphate and ternary lithium battery black powder according to claim 1 or 2, characterized in that: In step (9), the filtrate is concentrated to 1 / 5-1 / 20 of the original concentration; and / or, in step (9), the pH is adjusted to above 11; the heating temperature is increased to 80-99° C.; and the reaction is continued for 1-6 hours.

Citation Information

Patent Citations

  • A method for solid-phase electrolytic recovery of metal ions from lithium iron phosphate waste

    CN111411366B

  • Method for synergistically recovering positive electrode powder of waste lithium iron phosphate battery and waste ternary lithium ion battery

    CN115954574A

  • Method for recycling decommissioned lithium iron phosphate battery by electrochemical negative and positive coupling wet process

    CN117383588A

  • Method for combined leaching and recycling of waste lithium iron phosphate and ternary material positive electrode powder

    CN117821751A

  • Method for combined recovery of waste ternary lithium battery positive electrode powder and lithium iron phosphate battery positive electrode powder

    CN118398944A